Agricultural Extension Officers’ Knowledge and Perceptions of Food Security Issues in Trinidad and Tobago - T Grady Roberts; Wayne G Ganpat; Bertrhude Albert; Lendel Narine; Samantha Sudeen (Journal of International Agricultural and Extension Education, 2016)
Food security is a complex global problem that will require the interaction of a wide variety of people to solve. Although food insecurity has been reduced in Latin American and the Caribbean in the last decade, national governments in the region are still enacting policies to help further address the situation. In 2012,the government of Trinidad and Tobago enacted the National Food Production Action Plan and government extension agents are central to the field-level implementation of many aspects of the plan. This study explored agricultural extension officers’ knowledge and perceptions of food security issues in Trinidad and Tobago. Results revealed extension officers need additional professional development training to have the requisite knowledge to help implement the plan with the most pressing topics being data storage and retrieval; research and development; and understanding legislation and policies. Additionally, results revealed training needs varied for officers based on: (a) plans to stay in extension; (b) education level; (c) attention paid to global issues; and (d) training received on food security
Keywords: food security; extension; Caribbean; Trinidad and Tobago; agriculture